2005
DOI: 10.1523/jneurosci.3568-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with the Unfolded Protein Response Reveals a Role for Stargazin in Biosynthetic AMPA Receptor Transport

Abstract: The transmembrane protein stargazin enhances levels of functional AMPA receptors at the neuronal plasma membrane and at synapses. To clarify the mechanism for this effect, we studied trafficking of the AMPA receptor subunit glutamate receptor 1 (GluR1) in transfected COS7 cells. GluR1 expressed poorly on the surface of these cells and was primarily retained in the endoplasmic reticulum (ER). Stargazin expression strongly increased the surface fraction of GluR1. This effect was not reduced by a dominant-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 47 publications
(68 reference statements)
4
76
0
Order By: Relevance
“…More specifically, TARPs act as chaperones that prevent ER exit of incorrectly folded AMPARs 84 . Moreover, TARPs are essential for ER export of correctly assembled receptors 85 and remain part of the AMPAR complex throughout Golgi processing and forward trafficking to eventual surface expression at the postsynaptic density 86 . Similarly, cornichons have a welldefined role in the export of specific proteins from the ER 87,88 including AMPARs 89,90 .…”
Section: Rna Editing Ampar Assembly and Er Exitmentioning
confidence: 99%
“…More specifically, TARPs act as chaperones that prevent ER exit of incorrectly folded AMPARs 84 . Moreover, TARPs are essential for ER export of correctly assembled receptors 85 and remain part of the AMPAR complex throughout Golgi processing and forward trafficking to eventual surface expression at the postsynaptic density 86 . Similarly, cornichons have a welldefined role in the export of specific proteins from the ER 87,88 including AMPARs 89,90 .…”
Section: Rna Editing Ampar Assembly and Er Exitmentioning
confidence: 99%
“…The present study found that GluR2, but not GluR3, is attenuated at synapses in vivo and in vitro in a chronic manner. GluR1/2 heteromers are assembled in the endoplasmic reticulum, and the assembled hetero-tetramers remain as a functional unit while being transported into dendrites by vesicles (Vandenberghe et al, 2005). It is now well established that regulation of synaptic GluR1/2 trafficking is a complex, multifaceted process.…”
Section: Regulation Of Ampa Receptor Trafficking By Antimanic Agents mentioning
confidence: 99%
“…Two recent studies found the interaction of stargazin and other TARPs with AMPARs to be the most robust and least transient compared with other putative interactions, including those with 4.1 proteins (Fukata et al, 2005;Vandenberghe et al, 2005). Indeed, TARPs function as auxiliary subunits of AMPARs and are important determinants of AMPAR trafficking and synaptic anchoring.…”
Section: 1g/n Double Mutants Is Not Changedmentioning
confidence: 99%